2020
DOI: 10.1016/j.heliyon.2020.e05509
|View full text |Cite
|
Sign up to set email alerts
|

Transmission channels between financial development and CO2 emissions: A global perspective

Abstract: This paper aims to investigate the direct and indirect effects of financial development on CO2 emissions, using a global sample of 100 countries from 1990-2012. Our main contribution to the literature lies in the identification and explanation of possible transmission channels that allow financial development to affect environmental quality. The paper employs 2SLS and 3SLS estimators to investigate these channels. Empirical results confirm the positive direct effect of financial development on environmental de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 49 publications
3
44
0
7
Order By: Relevance
“…Hence, the significantly positive direct effect is taken over by the negative spillover impact of financial growth on CO 2 emission presenting a total effect which is significantly negative. The role of financial development in promoting business growth more than promoting technological progress and green projects increases energy consumption and is a possible explanation for this process, and the findings align with Bui (2020) and Charfeddine and Kahia (2019). Conversely, a unit rise in financial development of neighbouring countries suggests 12.5% decline in carbon emissions of the local country through the negatively significant spillover effect.…”
Section: Resultssupporting
confidence: 75%
“…Hence, the significantly positive direct effect is taken over by the negative spillover impact of financial growth on CO 2 emission presenting a total effect which is significantly negative. The role of financial development in promoting business growth more than promoting technological progress and green projects increases energy consumption and is a possible explanation for this process, and the findings align with Bui (2020) and Charfeddine and Kahia (2019). Conversely, a unit rise in financial development of neighbouring countries suggests 12.5% decline in carbon emissions of the local country through the negatively significant spillover effect.…”
Section: Resultssupporting
confidence: 75%
“…Consequently, the prospect of achieving environmental sustainability can be largely compromised. Conversely, a developed financial system could be beneficial for extending green finance, which can provide credit to firms keen to invest in energy-efficient production processes [ 17 , 18 ]. Furthermore, the financial services sector can also portray a central part in financing research and development-related projects to achieve technological innovations for environmental development [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their research found that R&D spending helps reduce CO 2 emissions, but energy consumption and financial development have led to environmental degradation. Bui [17] conducted a sample study of 100 countries from 1990 to 2012 and the empirical results confirmed the direct and positive impact of financial development on environmental degradation. In addition, two transmission channels from financial development to environmental quality have also been identified.…”
Section: Financial Development and Co 2 Emissionsmentioning
confidence: 72%